Envelhecer na contemporaneidade: subjetivações, modelos e resistências - Azevedo, Celina Dias (2018)
We provide a series of texts with the objective of discussing how aging is presented in contemporaneity, its subjectifications, its models based on the precepts of active aging – which permeate a large part of the reflections on aging –, and its guiding documents, as well as possible forms of resistance. The guiding questions were: How can the fear of disease, of frailty, of dependence, of old age, of a non-standard body be produced, mobilized and transformed into an engine of obedience to prescripts for a good aging? How do the demands of neoliberalism back the creation of a market of educational and cultural projects targeted at old people and establish the figure of the old person who is the Entrepreneur of him/herself as the model to grow old? In what way does the reflection on old age, preferably grounded on biological aspects and on health, neglect other dimensions of life and incorporate and strengthen the idea that life must be guided by knowledge and specialists who dictate norms to longevity, based on viewing the biological body as the object of an action that does not need the participation of the person who receives such action? The answers might be in one’s care for oneself, in the perception of singularity, in experimentation, in the construction of small forms of resistance in daily life. Thus, permanent education, health, control by means of fear, and the neoliberal notion of the entrepreneur of oneself were the axes selected to interrogate and visualize what lies beyond what is proposed by documents that prescribe active aging as the formula for a good aging. References to fragments of movies and literary works pervade the entire text and help in the construction of the current reflection. The fragments talk to each other, take root, and connect with the text in a creative flow, opening themselves to other reading possibilities and forming a multiple and diverse look that cuts paths and points to other directions. Spinoza, Nietzsche, Deleuze and Foucault, “philosophers of the potency of life”, have stimulated us to take philosophy as a tool, a lens for this observation